Homesickness in Dur E Aziz Amna's American Fever - Attiba, Khoirotul; Djohar, Hasnul Insani; Savira, Putri; Salsabila, Yasmina Shafa (Muslim English Literature, 2023)
This study discusses the main sources of homesickness among the characters as the loss of family and culture, the unattainable dream of returning home, and the challenges of adapting to a new environment. The research reveals factors causing homesickness experienced by diaspora characters, as seen in the protagonist of Dur e Aziz Amna’s American Fever. The researchers analyze the issues of homesickness with diaspora literary perspectives. This study engages with diaspora studies, especially Stuart Hall's theory of cultural identity and diaspora. The result shows that diaspora individuals typically have expectations and admiration of their cherished homeland to overcome their homesickness. The cultural differences, the expectation for home, and the unfamiliarity with the home create a longing for the homeland's homesickness. The more the characters spend time in the United States, the more they realize how distant it is from what they had expected about the beauty of their homeland. Thus, they keep admiring their homelands and accept the differences and unfamiliarity to overcome their homesickness.